Dynamics of an Aggressive Vocalization in the Common Loon (Gavia immer): A Review. - Mager, John N.; Walcott, Charles. (Tufts University. Tisch Library., 2019)
Unlike most waterbirds, Common Loons (Gavia immer) have a dynamic vocal repertoire that includes the high-amplitude wail, tremolo, and yodel. This paper is a review of the acoustic structure of the yodel, an aggressive warning signal only given by male Common Loons. The context in which males yodel is described along with the possible adaptive functions of this signal. The yodel is the most acoustically complex vocalization of the Common Loon and contains a wealth of information about the signaler. Suites of frequency and time elements of the yodel appear to communicate information about the identity of the signaler, which may be important for neighbor-stranger, mate, and kin recognition. The peak frequencies of the final note of the introductory phrase and repeat phrases also appear to communicate the condition-dependent fighting ability. Finally, the number of repeat phrases a male adds to its yodel appears to communicate the aggressive motivation, or the willingness a male Common Loon has to escalate a contest. Under various contexts not necessarily unique to Common Loons, these functions may be mutually beneficial to signalers and conspecific and heterospecific receivers, and evoke a number of interesting questions regarding the function of this dynamic signal. Such dynamic vocal signals are rare among waterbirds, and among ornithologists and behaviorists alike elicit questions regarding the conditions that maintain signal honesty among birds communicating fighting ability and aggressive state within the same vocal signal.